Making a Moral Society : Ethics and the State in Meiji Japan - Reitan, Richard M. (Book collections on Project MUSE., 2010)
Presents a study of ethics in Meiji Japan (1868-1912) that explores the struggle to define a common morality for the emerging nation-state. This book considers the fluidity of moral subjectivity by juxtaposing rinrigaku texts with moral writings by religious apologists.